2000
DOI: 10.1002/1521-396x(200005)179:1<125::aid-pssa125>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Threading Dislocation Reduction in Growing GaN Layers

Abstract: In this work, a model is developed to treat threading dislocation (TD) reduction in (0001) wurtzite epitaxial GaN thin films. The model is based on an approach originally proposed for (001) f.c.c. thin film growth and uses the concepts of mutual TD motion and reactions. We show that the experimentally observed slow TD reduction in GaN can be explained by low TD reaction probabilities due to TD line directions practically normal to the film surface. The behavior of screw dislocations in III-nitride films is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 28 publications
7
47
0
4
Order By: Relevance
“…Mathis et al 23 extended the model proposed by Speck et al 37 for cubic semiconductors into the case of wurzite GaN. According to this model efficiency and kinetics of dislocation reduction strongly depends on the initial dislocation distribution between different types of Burgers vectors.…”
Section: Extended Defects Misfit Dislocationssupporting
confidence: 69%
See 4 more Smart Citations
“…Mathis et al 23 extended the model proposed by Speck et al 37 for cubic semiconductors into the case of wurzite GaN. According to this model efficiency and kinetics of dislocation reduction strongly depends on the initial dislocation distribution between different types of Burgers vectors.…”
Section: Extended Defects Misfit Dislocationssupporting
confidence: 69%
“…However, these two papers seem to be somewhat contradictory. Mathis et al 23 concluded that there is an efficient reduction of threading dislocation density in films with a high fraction of mixed character dislocations since only such dislocations tend to be inclined. On the other hand, films with a high fraction of edge dislocations should not have significant dislocation reduction.…”
Section: Extended Defects Misfit Dislocationssupporting
confidence: 66%
See 3 more Smart Citations